The Effect of Endorphin Massage on Reducing Anxiety in Third-Trimester Pregnant Women in Purwakarta Regency, Indonesia - Hekmawati, Shanti (Archives of The Medicine and Case Reports, 2024)
Anxiety is an emotion commonly experienced by pregnant women, especially in the third-trimester. Anxiety can disrupt the physical and mental health of pregnant women and can have a negative impact on fetal development. Endorphin massage is a therapy that can be used to reduce anxiety in pregnant women. This study aims to determine the effect of endorphin massage in reducing anxiety in third-trimester pregnant women in Purwakarta Regency, Indonesia. This research uses a quasi-experimental research design with a pre-test and post-test approach. The research sample consisted of 60 third-trimester pregnant women who were divided into two groups, namely the treatment group (30 people) and the control group (30 people). The treatment group received endorphin massage therapy for 30 minutes 10 times, while the control group received no therapy. Anxiety data was measured using the state-trait anxiety inventory (STAI) questionnaire. The results showed that there was a significant difference in anxiety between the treatment group and the control group after receiving therapy (p < 0.05). Anxiety in the treatment group decreased significantly after receiving therapy, while anxiety in the control group did not change. Based on the results of this study, it can be concluded that endorphin massage is effective in reducing anxiety in third-trimester pregnant women.